Prevention of Tracheo-Innominate Artery Fistula Formation as a Complication of Tracheostomy: Two Case Reports - Byungsun Yoo; Bongjin Lee; June Dong Park; Seong Keun Kwon; Jae Gun Kwak (MDPI AG, 2022)
Tracheo-innominate artery fistula (TIF) is a rare complication of tracheostomy and refers to the formation of a fistula between the trachea and innominate artery. Because TIF is fatal, prevention rather than treatment is very important. Here we report the cases of two high-risk patients who underwent tracheostomy, and in whose cases attempts were made to lower the risk of TIF. In the first patient who developed a chest deformity with Duchenne muscular dystrophy, a tracheostomy was performed with a high-level (cricothyroid level) approach compared with the standard tracheostomy. In the second patient, the thoracic cage was relatively small due to a giant omphalocele, and the risk of a fistula forming was decreased by wrapping the innominate artery with an opened polytetrafluoroethylene vascular graft after resolving crowding of the intrathoracic cavity by total thymectomy. There was no TIF occurrence at the outpatient follow-up in either case. We expect that our approaches may be effective intervention measures for preventing TIF.